Discovery of New non-steroidal selective glucocorticoid receptor agonists. Issue 186 (February 2019) - Potamitis, Constantinos; Siakouli, Dimitra; Papavasileiou, Konstantinos D.; Boulaka, Athina; Ganou, Vassiliki; Roussaki, Marina; Calogeropoulou, Theodora; Zoumpoulakis, Panagiotis; Alexis, Michael N.; Zervou, Maria; Mitsiou, Dimitra J.
Graphical abstract: Highlights: Virtual Screening utilizing a structure-based pharmacophore model of GR-LBD. Discovery of two 1, 3-benzothiazole analogs (1 and13 ) acting as genuine SEGRA. 1 and13 transrepress a subset of NFKB targets genes in a GR-dependent manner. New proposed binding contacts of1 and13 at the extended cavity of GR-LBD. Abstract: Glucocorticoids (GCs) are widely used as potent anti-inflammatory drugs; however, GC therapy is often accompanied by adverse side effects. The anti-inflammatory action of GCs is exerted through the glucocorticoid receptor (GR) in part by antagonizing the pro-inflammatory nuclear factor k B (NF-kB) whereas the majority of side effects are assumed to be mediated by transactivation of GR target genes. We set out to identify novel non-steroidal selective GR agonists (SEGRA) favoring transrepression of NF-kB target genes over transactivation of genes associated with undesirable effects. Our virtual screening protocol was driven by a pharmacophore model based on a pyrrolidinone amide analogue (named as 'compound 12′ in Biggadike et al 2009, PNAS USA 106, 18, 114) bound to the extended binding pocket of the GR ligand binding domain (GR-LBD). Ambinter library (7.8 million compounds) was queried by our validated pharmacophore hypothesis and the prioritized compounds were biologically evaluated using a series of well-established screening assays. Two structurally similar hits (1 and13 ) were identified that bind to GR, induce its translocation to the nucleus, do not mediate transactivation of GR target genes whereas partially repress a number of pro-inflammatory NF-kB target genes, in a GR-dependent manner. Explanatory molecular dynamics (MD) calculations could detail the per-residue interactions accounting for the binding of1 and13 to the extended binding pocket of GR. The discovered 1, 3-benzothiazole analogs introduce a new class of genuine SEGRA paving the way for hit-to-lead optimization.